Does Vocational Training Promote Female Labour Force Participation? An Analysis for India. (February 2021) - Bairagya, Indrajit; Bhattacharya, Tulika; Tiwari, Pragati
The objective of the article is to assess the impact of formal and informal vocational training on female labour force participation in India, based on the Periodic Labour Force Survey data for 2017–2018, employing a trivariate probit model. Results show that participation both in formal and informal vocational training has a positive and statistically significant impact on female labour force participation across all specifications of the regression models, thus showing the robustness of the relationship. Most importantly, the provision of vocational training helps break the traditional U-shaped relationship between female labour force participation and educational levels. However, the fact that the percentage of formal vocational training holders is much lower than that of informal vocational training holders and that it varies among males and females, points to the need for special policy attention on the promotion of female participation in formal vocational training on a large scale. JEL Codes: J21, J24, J71